2013
DOI: 10.1007/s10433-013-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluid mechanics moderate the effect of implementation intentions on a health prospective memory task in older adults

Abstract: The aim of the present study was to test if a cognitive strategy improves older adults' prospective memory performance in a naturalistic health task. Moreover, it was tested if a possible strategy effect is moderated by individual differences. Therefore, a group of older adults was asked to perform a task taken from the medication adherence literature (i.e., blood pressure monitoring). Half of them were asked to form implementation intentions. Additionally, crystallized pragmatics and fluid mechanics, conscien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 57 publications
2
49
0
Order By: Relevance
“…Cognitive reserve describes the potential to compensate for age-related changes (e.g., age-related decline) through (lifelong) intellectual activities and environmental factors (Barulli and Stern 2013;Stern 2002). Our findings suggest that working memory training can be especially beneficial for older adults with reduced preconditions such as lower levels of crystallized intelligence (see also Brom et al 2014 for a similar finding on fluid intelligence).…”
Section: Discussionsupporting
confidence: 65%
“…Cognitive reserve describes the potential to compensate for age-related changes (e.g., age-related decline) through (lifelong) intellectual activities and environmental factors (Barulli and Stern 2013;Stern 2002). Our findings suggest that working memory training can be especially beneficial for older adults with reduced preconditions such as lower levels of crystallized intelligence (see also Brom et al 2014 for a similar finding on fluid intelligence).…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, relating our findings to the meta-analytic result for implementation intentions on health behavior by Gollwitzer and Sheeran (2006;d ϭ .59 [k ϭ 23]), our effect displays a similar strength. This is only the fourth study to investigate and reveal this effect of the implementation intention strategy on a real-life prospective memory task in old age, and therefore in concert with the previous studies (Bélanger-Gravel et al, 2013;Brom et al, 2013;Liu & Park, 2004) allowing a more generalized conclusion on the efficiency of the implementation intention strategy for older adults.…”
Section: Reducing Prospective Memory Task Demands: Strategy Trainingmentioning
confidence: 92%
“…Sessions 1 and 2 served as pre-and posttest assessment for the task-switching 1 Sample size was based on effect sizes from previous single intervention studies using either process training (e.g., Karbach & Kray, 2009;Zinke et al, 2012) or strategy training (Brom et al, 2013). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, failing to remember to perform a task after being asked to do so by a spouse or boss can, at the very least, lead to irritation and could lead to even more unpleasant outcomes. Thus, improving the ability to remember to perform these tasks could have important benefits in many situations and prior research has shown that PM can be improved through the application of a self-regulatory strategy known as implementation intentions (Brewer & Marsh, 2010; Brom, Schnitzspahn, Melzer, Franziska, & Kliegel, in press; Chasteen, Park, & Schwarz, 2001; Liu & Park, 2004; McDaniel, Howard, & Butler, 2008; McDaniel & Scullin, 2010; McFarland & Glisky, 2011, 2012; Meeks & Marsh, 2010; Schnitzspahn & Kliegel, 2009). …”
Section: Introductionmentioning
confidence: 99%